Modified Wheeler Technique with Inferior Lid Retractor Plication for Senile Entropion - Ul Kadir, Syeed Mehbub; Jahan, Farhat; Rahman, Md Tauhidur; Ahmed, Sharmin; Haider, Md Golam; Limbu, Ben (Nepalese Journal of Ophthalmology, 2022)
Introduction: The study aimed to assess the outcome of the modified wheeler technique with lower eyelid retractor plication for the correction of Involutional (senile) entropion among the study patients Materials and methods: A retrospective case series study was conducted in two tertiary eye hospitals of Bangladesh from 1 July to 31 December, 2020. This study included all patients undergoing modified wheeler technique with inferior lid retractor plication and followed up to at least one year and six months between 01 January 2015 to 31 December, 2019. All patients were suffering from senile entropion of the lower eyelid. All surgeries were performed by a single surgeon and the study sample size was selected purposively. Patients were operated by the modification of modified wheeler technique for the correction of lower eyelid entropion in this study. The outcome of the surgical techniques was assessed at regular intervals on each follow up. Results: Thirty eyes of thirty patients were evaluated. Success rate was 100% in the 18 months follow up time with no recurrence in any. Ecchymosis, skin scarring and/or minimal pain were observed as post-operative complications. Conclusion: The modified wheeler technique with inferior eyelid retractor plication is the definitive and permanent procedure for the correction of involutional entropion with minimal or no recurrence.